MAJOR PRINCIPLES OF EPILEPSY TREATMENT. ALGORITHM OF SELECTION OF ANTIEPILEPTIC DRUGS - K. Yu. Mukhin; O. A. Pylaeva; L. Yu. Glukhova; M. B. Mironov; M. Yu. Bobylova (Русский журнал детской неврологии, 2015)
The authors reviewed general principles of epilepsy treatment in details as well as provided their proprietary algorithm of selection of antiepileptic drugs developed Svt. Luka's Institute of Child Neurology and Epilepsy. This algorithm is designed for general practitioners that deal with treatment of epilepsy. In the course of selection of the first antiepileptic drug, the doctor must take into consideration the age of the patient, assess their level of development, clinical manifestations of seizures, data of electroencephalography and magnetic resonance imaging. The data received allows determination of the type of seizures, supposing of the syndrome-related diagnosis, and selection of the most appropriate antiepileptic drug of first choice in each specific case. There are also recommendations for further examination of patients and monitoring of efficacy of therapy.